RECOGNITION OF PALM FINGER MOVEMENTS ON THE BASIS OF EMG SIGNALS WITH THE APPLICATION OF WAVELETS - KRZYSZTOF KRYSZTOFORSKI; ANDRZEJ WOLCZOWSKI; ROMUALD BĘDZIŃSKI; KRZYSZTOF HELT (TASK Quarterly, 2004)
The paper describes an EMG signal analysis based on the wavelet transform, applied for the hand prosthesis control. Signal features are represented by wavelet coefficients. A cross-validation method is applied for the feature selection process. The classification algorithm uses multistage recognition. The information about finger posture provided by a data glove is recorded concurrently with forearm EMG signals. The acquired data are used to train the classification algorithm.